Highly sensitive ultra-thin optical CO2 gas sensors using nanowall honeycomb structure and plasmonic nanoparticles - Elrashidi, Ali; Traversa, Enrico; Elzein, Basma (Frontiers in Energy Research, 2022)
The carbon dioxide highly sensitive ultra-thin optical sensor using plasmonic nanoparticles distributed uniformly on the nanowall honeycomb structure with a footprint in the millimeter range is presented in this work. The zinc oxide (ZnO) honeycomb nanowall structure is grown by the pulsed laser deposition (PLD) method. Moreover, the performance of the fabricated structure as a gas nanosensor is simulated using the finite difference time domain (FDTD) method in the visible and near-infrared regions. A graphene layer is mounted on the top of the nanowall, and then, plasmonic nanoparticles are distributed on the nanowall sides. Furthermore, the effect of gas concentration on the pressure and consequently on the dielectric constant of the gas are also illustrated in this article. Red-shift in the absorption has been noticed with different refractive indices and intensity sensitivities. The obtained refractive index sensitivity of the proposed nano optical sensor is 874 nm/RIU, and the intensity sensitivity is 5,174 RIU−1 with the figure of merit of 12.5 and quality factor (Q-factor) of 281 at a carbon dioxide (CO2) concentration of 5,500 ppm. Finally, the absorbed power of the incident light is calculated using different polarization angles, from 10° to 80° with a step10°.